Blended Learning in English Academic Reading to Respond Revolution 4.0 - Harpiansi Harpiansi; Nyayu Yayu Suryani (Universitas Hamzanwadi, 2019)
The 4th industrial revolution effects many areas in today’s global era, including higher institution. Internet is the main instrument in this revloution. The limitation of time room availibility of the students will accor if the schools appliy face to face only in leaarning process. Blended learning is the alternative solution to overcome the case of inavility time and palce to learn. In addition to developing distance universities should also equip students with English reading skill. This study is aimed at describing the effect of blended learning on English academic reading by using experimental method with pretest-posttest control design. The sample of this research is 32 students of AMIK Bina Sriwijaya. The data were collected through English reading comprehension test in the form of multiple choice and were analyzed by using Independent Sample T test. Based on the Independent Sample T test output table in the Equal variances assumed section, it is found that Sig values. (2 tailed) of 0.0010.05.It can be concluded that there is a significant difference between the average learning outcomes of respondents in the experimental group and respondents in the control group. In other word, there is significant effect of blended learning on students reading skill achievement.